Streptococcal Pneumoniae Mycotic Aneurysm: : A Rare Case of Disseminated Pneumococcal Disease in an Immunocompetent Host (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Infectious Diseases; Case Report